2015
DOI: 10.1002/jor.22955
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale strain analysis of tendon subjected to shear and compression demonstrates strain attenuation, fiber sliding, and reorganization

Abstract: ABSTRACT:The manner in which strains are passed down the hierarchical length scales of tendons dictates how cells within the collagen network regulate the tissue response to loading. How tendons deform in different hierarchical levels under shear and compression is unknown. The aims of this study were: (i) to evaluate whether specific regions of bovine deep digital flexor tendons exhibited different strain attenuation from macro to micro length scales, and (ii) to elucidate mechanisms responsible for tendon de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 35 publications
(77 reference statements)
2
35
0
Order By: Relevance
“…Our work showed that sliding between collagen fibers primarily regulated the mechanical response of distal and proximal regions from deep digital flexor tendon (DDFT) subjected to shear loading . Different from the response to shear, DDFT showed both fiber realignment and sliding as physical mechanisms governing the mechanical response in compression …”
Section: Contribution Of Tendon Structure To Mechanicsmentioning
confidence: 90%
See 3 more Smart Citations
“…Our work showed that sliding between collagen fibers primarily regulated the mechanical response of distal and proximal regions from deep digital flexor tendon (DDFT) subjected to shear loading . Different from the response to shear, DDFT showed both fiber realignment and sliding as physical mechanisms governing the mechanical response in compression …”
Section: Contribution Of Tendon Structure To Mechanicsmentioning
confidence: 90%
“…(A) D‐period change of mouse SST during static tensile loading and AFM‐acquired images measuring fibril D‐period with line highlighted (adapted, with permission, from Connizzo et al). (B) A measure of microscale fiber sliding, termed between rows rotation, increased with increasing applied shear strain, while images taken via multi‐photon microscopy showed fiber sliding during shear stress relaxation testing (white arrows denote photobleached lines broken due to fiber sliding; adapted, with permission, from Fang et al). (C) Crimp frequency of tendon in tensile loading decreased from the toe to linear regions of the stress‐strain curve and representative images of polarized light showing the change of crimp pattern (adapted, with permission, from Miller et al).…”
Section: Contribution Of Tendon Structure To Mechanicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, the sliding mechanism prevails in the connective tissues of human and other animals [114]—sliding of collagen fibre bundles, i.e., fascicles, has been observed [115,116] during tissue deformation. For a MCT to change from a compliant to a stiffened state and vice versa, other mechanisms would be involved in regulating this transition process.…”
Section: Collagen Fibril Biomechanicsmentioning
confidence: 99%